KOMUNIKASI PEMBANGUNAN MELALUI MUSYAWARAH RENCANA PEMBANGUNAN (MUSRENBANG) KABUPATEN ACEH UTARA - Mildad, Jamal (SOURCE : Jurnal Ilmu Komunikasi, 2016)
This study aims to find out the government commucation system throght Musrenbang (Musyawarah Rencana Pembangunan - Development Plan Discussion) in the devolopment  north Aceh community’s religiosity. The data were collected throght intensive imnterviews whit related figures, such as the head of North Aceh Bappeda, non-government organization leaders, north Aceh Community leaders, as well as the head of Ulama consultation Council (Majelis Permusyawartan Ulama) – MPU, who also is religious leader in North Aceh Regency. Data were also colleted through field observation. The study also revealed that the government communicates primerly (directly) with society through advice conveyed through Musrenbang, than the government communicates secondarily (indirectly) through mass media. The communicator of relegion to north Aceh society is the ulama, subdistrict and village personnels, MPU, religious and traditional figure. The government is facilitator  for society’s communication. The advice given are the elimination of vices, the upholding of Islamic law, the mastery of religious studies, and the strengthening of family. The result of north Aceh gavernment and society communication is not yet optimal. The quality of religion life as well as the infrastructure to increase this quality is not yet sufficient as society has’nt utilized the  mosque  optimally. Religious teaching as value is not yet understood, internalized, and acted upon by society in daily life. Negative and deviant behavior, far from religious, normative, and ethical injuctions, often occur. The problem above is due to stumbling blocks such as the weak human resource of development communicator. The reason is the limitation of fund for religious development be it in the physical aspects as well as the lack of society’s role in development. Keywords: Government Commucation, Development Plan Discussion, and Mass Media